IMF Staff papers : Volume 40 No. 2. (IMF Staff Papers; IMF Staff Papers, 1993)
The relationship between the degree of wage indexation chosen by private agents and the degree of public debt indexation chosen by the government is examined. It is shown that the government is likely to increase public debt indexation in response to an increase in wage indexation. By contrast, higher public debt indexation has an ambiguous effect on wage indexation. In equilibrium, wage and public debt indexation may be positively or negatively related. This relationship is analyzed in situations where the policymakers can precommit to policies and in those they cannot.